Profil Self Regulated Learning Siswa SMA “X” di Jember Selama Masa School From Home (SFH) - Anggraeni Swastika Sari; Ria Wiyatfi Linsiya (Universitas Muhammadiyah Jember, 2022)
This study aims to provide an overview of Self Regulated Learning for higt school student “X” in Jember during the pandemic. The method used is descriptive quantitative. The research subjects were high school students with a sample of 166 students. The technique used is random sampling using google form. The results of the validity of the Self-Regulated Learning scale are between 0.257 to 0.695 with a reliability value of 0.801. Based on the category, the Self Regulated Learning of higt school student